KAJIAN ANALISIS RISIKO BENCANA TANAH LONGSOR SEBAGAI DASAR DALAM PEMBANGUNAN INFRASTRUKTUR DI DESA SRIHARJO KECAMATAN IMOGIRI KABUPATEN BANTUL - Sri Aminatun (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2017)
Sriharjo Village Imogiri District Bantul Regency is one of the villages that are vulnerable to landslides located on the morphology of the ridge to the hills in the eastern region of Bantul Regency. In each rainy season some areas in the village of Sriharjo landslides occurred. Basedon the map of landslide incident from the Regional Disaster Management Agency in 2011, Sriharjo village is one of the villages in Bantul Regency that experienced high intensity of landslide events, one of the ways to mitigate the landslide disaster is to assess and analyze the risk of landslide disaster in detail. This study aims to identify the homes of residents who are in landslide threat zone, be it a high threat zone or medium threat zone. The method used in this research is descriptive method with qualitative approach combined with quantitative method used to give a clear picture about the number of houses in each zonation. Sources of data used are primary and secondary data sources through interviews and documentation. The results of this study indicate that 1) the number of households in the high risk zone is 119 houses, in the yellow risk zone is 136 houses. 2) The village of Sriharjo has a high threat, medium to high vulnerability, and medium capacity, which means having a medium to high risk. 3) Recommended infrastructure development for disaster mitigation.